Hyperlipidemia in adult, pediatric and diabetic renal transplant recipients - Ibels, Lloyd S; Alfrey, Alle C; Weil, Richard (The American journal of medicine, 1978)
Serum cholesterol and triglyceride concentrations were measured and lipoprotein electrophoreses were performed on serum samples from 175 adult, 19 pediatric and 11 diabetic transplant recipients and from 102 healthy volunteer subjects. Serum lipids were also measured in 14 patients prior to and for 40 weeks following transplantation. p]The mean serum cholesterol and triglyceride concentrations were greater in all three groups of transplant recipients than in the healthy volunteer subjects but there were no differences in serum lipids between any two of the transplant recipient groups. Sixty-one per cent (125) of the patients had hyperlipidemia. Lipoprotein electrophoreses demonstrated that the hyperlipoproteinemia was heterogeneous, 26 per cent (46) of the patients had type IV hyperlipoproteinemla, 23 per cent (39) type 11b and 11 per cent (19) type 11 A. Serum lipid concentrations in patients receiving alternate-day corticosterold therapy were not different from those receiving daily corticosterold therapy. Positive correlations were found between serum triglyceride concentrations and the daily prednlsone dosage, relative body weight, serum creatinine and blood glucose concentrations. No correlation was found between prednlsone dosage and the latter three variables. A positive correlation was also found between serum triglycerides and relative body weight in the healthy volunteer subjects, but for any given body weight serum triglycerides were significantly greater in the transplant recipients. Transplant recipients with hypercholesterolemla were receiving a larger prednisone dosage than those with normal serum cholesterol levels. Serum cholesterol and triglyceride levels became abnormal within eight weeks of transplantation and remained abnormal throughout the remaining 32 weeks during which these patients were followed. Correlations were found between serum cholesterol and triglyceride levels and the cumulative dose of prednisone during this 40 week period. It is concluded that hyperllpidemla is very common in renal transplant recipients, is a mixture of types 11 A, 11B and IV hyperlipoprotelnemla, is equally prevalent in diabetic, pediatric and adult transplant recipients and is not diminished by the use of alternateday cortlcosteroids. Prednisone dosage, obesity and the degree of Impairment of graft function appear to be responsible for hypertriglycerldemia; prednlsone dosage appears to be responsible for hypercholesterolemla. Serum lipid abnormalities develop within eight weeks of transplantation and can be related to the cumulative dose of prednisone in the early post-transplant period.